Advancement in organizational behaviour: Essays in honour of Derek S. Pugh - CLARK, Timothy Adrian Robert (Institutional Knowledge at Singapore Management University, 1997)
Organization behaviour (OB) is a relatively recent and still growing area of academic enquiry having only emerged since the 1950s. This book is a collection of essays to mark the retirement of Derek Pugh - one of the most influential scholars in the field.